The Serabit Expedition of 1930: III. The Temple of Hathor - New, Silva (Harvard theological review, 1932)
On one of the relatively flat projections of the plateau which forms the top of the mountain of Serabit el-Khadim, three days’ journey by camel from the nearest point of the coast into the interior of the peninsula of Sinai, stand the ruins of the Temple of Hathor. Near it are turquoise mines exploited by the Egyptians from the third to the eighteenth dynasties, and probably also worked intermittently by the local tribes. But the mines were not the raison d'être of the temple, although the goddess of the temple was certainly worshipped by the miners. In the Wadi Maghara also there are Egyptian turquoise mines, and until they were either destroyed or taken away to museums there were inscriptions, carved to record Egyptian expeditions to them. But there is no temple at Maghara.